Health Strategy in a Post-Crisis, Decentralizing Indonesia - World Bank (Washington, DC, 2013)
The study reviews the strategy for a prospective health development, and the health benefits associated with decentralization, in a likely challenging near to medium term period in Indonesia. It addresses the major government reorganization, expected to take effect in January 2001, which could well define the social process during the next decade, consisting of decentralization of spending authority, enhanced access to resources at local government levels, and civil service reform. The potential health system benefits, associated with decentralization, will enable citizens to become involved systematically in decisions regarding health policy, design, and financing, as well as influencing service provision. The report describes the health system performance, and costs in the country, namely an adaptation of health for all, aimed at a wide coverage, featuring integrated service provision at the primary health level. However, mixed results proved great imbalances, for low income families lagged behind other quintiles in terms of infant mortality rates, prevalence of specific diseases, and nutrition problems, while households in the top expenditure distribution, proved high uses of public facilities, compared to the bottom expenditure distribution. The pre-crisis policy is examined, i.e., the impacts on the provider-client equation; and, policy options offer opportunities through decentralization, reform related issues, and effective partnerships with non-governmental organizations, and donors.